PENGARUH MEDIA PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG DIARE PADA ANAK DI PUSKESMAS BATU AJI KOTA BATAM 2018 - Indriasari .; Nopri Esmeralda (Universitas Batam, 2019)
According to data from the Indonesian Ministry of Health diarrhea is still one of the main public health problems. This is caused by the high rate of illness and causes many deaths, especially in infants and toddlers often and often causes extraordinary events. according to the Batam City Health Department Data Report states that the incidence of diarrhea in 2011 was 60,670 cases and those receiving treatment in health services were 30,556 cases. Diarrhea is an environmental disease. There are two dominant factors, namely clean water facilities and faeces disposal. Both of these factors affect the knowledge and attitudes of mothers with the incidence of diarrhea in children. The mother's knowledge and the mother's attitude are very influential in the occurrence of diarrhea. If your knowledge is good, then you will know how to treat sick diarrhea at home and you will also know about the signs to bring your child to seek treatment or to refer to a health facility. Some health services carried out at the community one of them conduct counseling to cope with the incidence of diarrhea and change the behavior of people who still do not understand the importance of a clean environment to be free from disease. This research is a type of quantitative research. With a quasi-experimental research design. This research was conducted at Batu Aji Public Health Center in Batam City in July 2018. The population in this study was mothers who had children and went to Batu Aji Health Center in 2018. The population of this study consisted of 80 respondents with a sample of 40 in the experimental group and 40 in the group control. data processing using computerization. Then the data were analyzed by Univariate and Bivariate with paired T-Tests. The results of this study were obtained in the experimental group who were given counseling with an average value higher than the control group while the paired T-Test results showed a P-Value of 0,000 for the level of knowledge and attitude so that we can state that there is an influence counseling on the level of knowledge and attitudes. There is an influence of counseling media on the level of knowledge and attitudes of mothers about diarrhea in children in the Batam Aji Puskesmas